Pemberdayaan Kader Kesehatan tentang Komplementer Aromatheraphy Lemon Untuk Mengatasi Mual Muntah Pada Ibu Hamil Trimester I - Lutfiana Puspita Sari; Triwik Sri Mulati; Dian Ayu Pramukawati (Poltekkes Kemenkes Surakarta, 2024)
Background: Nausea and vomiting in pregnancy, generally called emesis gravidarum. Emesis gravidarum is among the most common discomforts experienced during early pregnancy, and it is complained about by 50-70% of pregnant women within the first 16 weeks. The impact of unmanaged emesis gravidarum can lead to the mother's body becoming weak, a pale complexion, and a drastic decrease in urinary frequency. Health cadres, as key figures in society with knowledge and skills in assisting with the management of first-trimester maternal emesis gravidarum, are expected to provide support to pregnant mothers in addressing these complaints. Methods: This community service used a clinical approach of lectures, discussions, and demonstrations for 98 health cadres and pregnant women in the South Klaten Community Health Center area. Conducted from May to July 2023, the program consisted of four monthly sessions totalling 12 hours, incorporating a pre-and post-test design to assess knowledge improvement. Evaluations began from the second session onward. Results: After training on lemon aromatherapy to alleviate emesis gravidarum in first-trimester pregnant mothers, the knowledge of the health cadres increases. This improvement can be observed through pre- and post-test scores, where the average pre-test score was 5-7 and the post-test score increased to 8-10. The outcome of this community service project is a scientific publication in an accredited national community service journal. Conclusion: Training for health cadres effectively to enhance their knowledge of lemon aromatherapy for reducing emesis gravidarum in first-trimester pregnant mothers.